PENGARUH KOMPETENSI PEDAGOGIK GURU TERHADAP HASIL BELAJAR SISWA PROGRAM KEAHLIAN AKUNTANSI DI SMK NEGERI 6 MAKASSAR - Nirmawati Nirmawati; Muhammad Azis; Hariany Idris (Kurikula : Jurnal Pendidikan, 2023)
ABSTRACT: In the accounting expertise program at SMK Negeri 6 Makassar, the purpose of thisstudy is to ascertain the impact of teachers' pedagogical competency on students' accountinglearning results. Learning outcomes and pedagogical competency of the teacher serve as the study's independent and dependent variables, respectively. All of the students in SMK Negeri 6 Makassar's accounting expertise program made up the study's population. A proportionate stratified random sample method was employed for the sampling process. Using a sample of 71 pupils, samples from the complete population were gathered. Both questionnaires and documents are utilized as data collection methods. Descriptive analysis of percentages, instrument testing, and hypothesis testing are the data analytic techniques used. According to the findings of a straightforward linear regression analysis, the teacher's pedagogic competence was calculated as Y = 59.055 + 0.325X, meaning that learning outcomes rose by 0.325 units for every additional teacher's pedagogic competency value. While the product moment correlation analysis yielded a correlation coefficient of 0.582 and a positive value at the range of 0.400-0.599, which is in the sufficient group, this indicates that the influence of teacher pedagogic ability on learning outcomes is sufficient.According to the analysis of the coefficient of determination (r), the value of (r) = 0.339, or 33.9%,indicates that the teacher's pedagogical expertise contributes to learning outcomes to the extent of 33.9%, with other factors influencing the remaining 66.1%. The hypothesis is "accepted" since the results of the t-test showed a significant value of 0.000 0.05, indicating that the teacher'spedagogical skill has a favorable and significant impact on learning outcomes.